Ingestion of Foreign Bodies in Orthodontics: A Literature Review - Covarrubias, María Elisa (2023)
Ingestion of dental foreign bodies is a complication that patients of dentists, particularly orthodontists, may encounter. Although uncommon, these incidents can pose life-threatening risks to patients, including airway obstruction and gastrointestinal damage. This review examines case reports of patients who have ingested orthodontic foreign bodies, whether it occurred within or outside the orthodontic setting. General and specific preventive recommendations, as well as initial management approaches for these complications, are reviewed.